It's Thanksgiving - Prelutsky, Jack (Greenwillow read-alone books, 1982)
Presents twelve poems about Thanksgiving, including "When Daddy carves the Turkey," "I Ate Too Much," "Daddy's Football Game," and "If Turkeys Thought."